Multiple Evidences for Association between Cognitive Impairment and Dysglycemia in Parkinson’s Disease: Implications for Clinical Practice - Yang, Liu; Chen, Zhilin; Li, Bo; Wang, Meihua; Yu, Lijia; Wan, Ying; Gan, Jing; Zhang, Yu; Liu, Zhenguo; Wang, Xijin (Frontiers in Aging Neuroscience, 2017)
Abstract Background and purpose: It remains unclear about the etiopathogenesis of cognitive impairment (CI) in Parkinson’s disease (PD). Since diabetes mellitus (DM) has been shown to be associated with CI in several diseases, we examined the association between CI and dysglycemia in PD. Methods: Enrolled PD patients completed a series of clinical and neuropsychological assessments. Motor symptoms were determined by Hohen-Yahr staging（H-Y staging）and Unified Parkinson's Disease Rating Scale – motor score (UPDRS-III). Neuropsychological functions were evaluated by the MiniMental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA), and the Hamilton Anxiety and Depression Scales. Moreover, fasting glucose, fasting insulin, glycosylated hemoglobin A1c (HbA1c) and oral glucose tolerance test were performed to assess glucose metabolism. Results: MoCA and MMSE scores in PD patients with DM group (PD-DM) were significantly lower than those in PD patients without DM group (PD-nDM). Consistently, PD-DM group showed significantly higher constituent ratio of CI than PD-nDM group. In addition, MoCA scores in HbA1c≥6.5% group and HbA1c≥7% group were significantly lower than those in the corresponding control groups. MoCA score in IR≥3 group was significantly lower than that in IR<3 group. Furthermore, MoCA score was negatively correlated with H-Y staging, HbA1c and insulin resistance, respectively. Finally, regression analysis indicated that H-Y staging and HbA1c≥7% were independent risk factors of CI in PD. Conclusions: CI may be tightly associated with dysglycemia in, at least partially, PD patients. Importantly, H-Y staging and HbA1c ≥7%, two independent risk factors of CI in PD, may serve as key biomarkers in future PD clinical practice.